Influence of iron on modulation of the antioxidant system in rat brains exposed to lead - Freitas Ferreira, Maria Cecilia de; Zucki, Fernanda; Duarte, Josilene Luciene; Iano, Flavia Godoy; Ximenes, Valdecir Farias [UNESP]; Rabelo Buzalaf, Marilia Afonso; Oliveira, Rodrigo Cardoso de (Wiley-Blackwell, 2017)
The objective of this study was to evaluate markers of oxidative stress in the brains of rats exposed to lead acetate (Pb(C2H3O2)(2)), either associated or not associated with ferrous sulfate (FeSO4). A total of 36 weaning rats (Rattus norvegicus) were divided into 6 groups of six animals and exposed to lead acetate for six weeks. In the control group (control), the animals received deionized water. The Pb260 and Pb260+Fe received 260 mu M lead acetate, and the Pb1050 and Pb1050+Fe received 1050 mu M lead acetate. The Pb260+Fe and Pb1050+Fe were supplemented with 20 mg of ferrous sulfate/Kg body weight every 2 days. Group Fe received deionized water and ferrous sulfate. The rat brains were collected to analyze the enzymatic activity of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and the concentration of reduced glutathione (GSH), lipid peroxidation (TBARS), and total antioxidant substance (TAS) (DPPH center dot technique). The activity of SOD and GPx in the experimental groups decreased compared to the control, together with the concentration of GSH (p<0.05). For CAT analysis, SOD tended to increase in concentration in the experimental groups without a concomitant exposure to FeSO4, whereas GPx showed a slight tendency to increase in activity compared to the control. For TAS-DPPH center dot, there was a decrease in the experimental groups (p<0.05). According to the results, SOD, GPx, and GSH were affected by lead acetate and exposure to ferrous sulfate changed this dynamic. However, further studies are needed to verify whether ferrous sulfate acts as a protectant against the toxic effects of lead. (C) 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 813-822, 2017.
Keywords: lead; ferrous sulfate; brain; antioxidants; catalase